EXCITATORY AND INHIBITORY INPUTS CONTRIBUTE TO LONG-LASTING PLASTICITY IN A REWARD LEARNING CIRCUIT. - Copenhaver, Ashley Elizabeth (My University, 2025)
The brain continuously integrates diverse streams of information to guide behavior, allowing organisms to adapt to an ever-changing world. This integration relies on dynamic changes in synaptic function, called synaptic plasticity, which underlie learning, decision-making, and emotional regulation. These changes have also been implicated in the pathophysiology of several neuropsychiatric disorders. Despite the clear importance of synaptic plasticity in mediating behavior, the molecular mechanisms driving this fundamental property remain unclear, limiting our understanding of the neurobiological basis of behavior and neuropsychiatric disorders. To address this gap, I studied the nucleus accumbens (NAc), a central hub that integrates cognitive, emotional, and reward-related information to drive motivated behaviors. I focused on the hippocampus (Hipp)-NAc pathway as it exhibits behaviorally relevant plasticity and conveys multiple types of information essential for reward-related behaviors. My work explored two key questions: What molecular mechanisms drive plasticity at Hipp-NAc synapses? and, how are diverse signals integrated within the NAc?Bidirectional regulation of Hipp-NAc synaptic strength mediates motivated behaviors, but how this regulation differs between sexes is largely unexplored despite well-established sex differences in motivated behaviors across species. Here, I identified multiple sex-specific and sex-similar mechanisms driving LTP at Hipp-NAc synapses. Furthermore, I demonstrated that chronic stress alters these synapses differently in males and females, uncovering a novel functional role for GABA B receptors in the process. I, then, expanded my scope to examine interactions between excitatory and inhibitory signals that may regulate the integration of spatial, contextual, and emotional information. My findings demonstrated key synaptic interactions occurring between distinct excitatory inputs to the NAc and revealed that inhibition plays a crucial role in modulating and enabling LTP at Hipp-NAc synapses. Lastly, I used computational approaches to improve Izhikevich model simulations and examine how biological sex, inhibition, and stress impact neuron dynamics. Overall, my work established key sex-specific mechanisms regulating Hipp-NAc plasticity, novel interactions between diverse signals in the NAc, and a computational framework to explore how various factors influence neuronal properties. These findings provide fundamental insight into how the brain transforms experience into behavior, advancing understanding of neural circuit function and informing targeted interventions for neuropsychiatric disorders.
Keywords: heterosynaptic plasticity; hippocampus; information integration; nucleus accumbens; reward; synaptic plasticity